Thirty Years of Flexible Job-Shop Scheduling: A Bibliometric Study - Coelho, Pedro (2021)
Industry 4.0 introduced a new change in paradigms and technologies in the industry. In the shop schedule, it gains a holistic viewpoint and online demands, real-time and reactive methodologies. Developments in the scheduling area are critical to success. First addressed by Brucker and Schlie in 1990, the Flexible Job-Shop Scheduling Problem has been attracting researchers and practitioners over the last decades. This body of research may be helpful to address the industry high flexibility scheduling problems. This article uses a bibliometric approach to study three decades of research on this problem. The main results identify the most prolific research areas, journals, institutions, countries, and authors, and co-citation networks that revealed the most influential authors, as well as their most relevant works. A conceptual analysis based on keywords burst and occurrences helped to identify the latest research evolution and trends; allowing to recognize alignments and gaps within Industry 4.0.